MicroRNA and Degradome Profiling Uncover Defense Response of Fraxinus velutina Torr. to Salt Stress - Liu, Jian Ning; Ma, Xinmei; Yan, Liping; Liang, Qiang; Fang, Hongcheng; Wang, Changxi; Dong, Yuhui; Chai, Zejia; Zhou, Rui; Bao, Yan; Wang, Lichang; Gai, Shasha; et al. (Frontiers in Plant Science, 2022)
Soil salinization is a major environmental problem that seriously threatens the sustainable development of regional ecosystems and local economies. Fraxinus velutina Torr is an excellent salt-tolerant tree species, which is widely planted in the saline-alkaline soils in China. A growing body of evidence shows that microRNAs (miRNAs) play important roles in the defense response of plants to salt stress; however, how miRNAs in F. velutina exert anti-salt stress remains unclear. We previously identified two contrasting F. velutina cuttings clones, salt-tolerant (R7) and salt-sensitive (S4) and found that R7 exhibits higher salt tolerance than S4. To identify salt-responsive miRNAs and their target genes, the leaves and roots of R7 and S4 exposed to salt stress were subjected to miRNA and degradome sequencing analysis. The results showed that compared with S4, R7 showed 89 and 138 differentially expressed miRNAs in leaves and roots, respectively. Specifically, in R7 leaves, miR164d, miR171b/c, miR396a, and miR160g targeting NAC1, SCL22, GRF1, and ARF18, respectively, were involved in salt tolerance. In R7 roots, miR396a, miR156a/b, miR8175, miR319a/d, and miR393a targeting TGA2.3, SBP14, GR-RBP, TCP2/4, and TIR1, respectively, participated in salt stress responses. Taken together, the findings presented here revealed the key regulatory network of miRNAs in R7 responding to salt stress, thereby providing new insights into improving salt tolerance of F. velutina through miRNA manipulation.